2019
DOI: 10.1101/2019.12.23.887059
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Drosophila PDGF/VEGF signaling from muscles to hepatocyte-like cells protects against obesity

Abstract: Highlights:• Muscle specific Pvf1 protects mature adult flies from obesity • Single-nuclei RNA sequencing reveals that PvR, the receptor for Pvf1, is highly expressed in the Drosophila hepatocyte-like cells/oenocytes.• PvR is required specifically in oenocytes to protect adult flies from obesity• Muscle-to-oenocyte Pvf1 signaling activates PvR/Pi3K/Akt1/mTOR in the oenocytes to suppress lipid synthesis• Muscle-derived Pvf1 helps terminate the rapid expansion of adipose tissue lipid stores in newly eclosed flie… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 87 publications
0
5
0
Order By: Relevance
“…For scRNA-seq, specific cell types may be susceptible to damage-induced cell death and will be removed before cell capture, while for snRNA-seq, all nuclei will be applied; (c) large and fragile cells, such as adipocytes, may not easily flow into microfluidics-based channels, including 10× Genomics, but their nuclei should be easily captured. Ghosh et al (2019) has recently reported the application of snRNA-seq for profiling adult fly abdominal cuticles. We have recently developed a reliable snRNA-seq protocol in Drosophila through both Smart-seq2 and 10× Genomics for profiling adult olfactory neurons (Li, McLaughlin, Luo, unpublished) and expect more snRNA-seq to be performed in other adult Drosophila tissues.…”
Section: Challenges Opportunities and Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…For scRNA-seq, specific cell types may be susceptible to damage-induced cell death and will be removed before cell capture, while for snRNA-seq, all nuclei will be applied; (c) large and fragile cells, such as adipocytes, may not easily flow into microfluidics-based channels, including 10× Genomics, but their nuclei should be easily captured. Ghosh et al (2019) has recently reported the application of snRNA-seq for profiling adult fly abdominal cuticles. We have recently developed a reliable snRNA-seq protocol in Drosophila through both Smart-seq2 and 10× Genomics for profiling adult olfactory neurons (Li, McLaughlin, Luo, unpublished) and expect more snRNA-seq to be performed in other adult Drosophila tissues.…”
Section: Challenges Opportunities and Perspectivesmentioning
confidence: 99%
“…Combining scRNA-seq with powerful genetic tools holds a great potential for making new discoveries. Indeed, recent scRNA-seq studies in Drosophila have revealed novel biological findings, such as characterizing new cell types in different tissues including the whole embryo, whole brain, ventral nerve cord, gut, blood, abdominal cuticle, testis, and ovary (Allen et al, 2020;Brunet Avalos, Maier, Bruggmann, & Sprecher, 2019;Cattenoz et al, 2020;Cho et al, 2020;Croset, Treiber, & Waddell, 2018;Davie et al, 2018;Fu, Huang, Zhang, Leemput, & Han, 2020;Ghosh et al, 2019;Guo et al, 2019;Hung et al, 2020;Jevitt et al, 2020;Karaiskos et al, 2017;Rust et al, 2019;Shin, Jones, Petkau, Panteluk, & Foley, 2019;Slaidina, Banisch, Gupta, & Lehmann, 2020;Tattikota et al, 2020;Witt, Benjamin, Svetec, & Zhao, 2019), revealing unrealized mechanisms underlying neural development and brain aging (Davie et al, 2018;Konstantinides et al, 2018;Kurmangaliyev, Yoo, LoCascio, & Zipursky, 2019;Li et al, 2017, and uncovering transcriptional regulation or signaling pathways controlling development and tumorigenesis (Ariss, Islam, Critcher, Zappia, & Frolov, 2018;Deng et al, 2019;Genovese et al, 2019;Ji et al, 2019). So far, scRNA-seq profiling has been performed in various Drosophila tissues from multiple stages (Figure 1 and Table 1), providing valuable resources for future studies of those individual tissues or tissue-tissue interactions.…”
mentioning
confidence: 99%
“…Oenocytes express the Pvf1 receptor PvR, and activation of PvR in oenocytes results in activation of mTOR which in turn leads to increased PI3K and Akt. This Pvf1-mTOR-Akt signaling cascade from muscle to oenocytes slows the rate of lipid synthesis without affecting the rate of lipid mobilization (Ghosh et al, 2020; Figure 2). The rate of lipid synthesis is very rapid in young flies, and Pvf1 expression levels are found to be very low at the time of eclosion.…”
Section: The Role Of Muscle In Maintaining Lipid Homeostasismentioning
confidence: 99%
“…The rate of lipid synthesis is very rapid in young flies, and Pvf1 expression levels are found to be very low at the time of eclosion. Overexpression of Pvf1 in young flies results in inhibition of developmentally programmed TAG synthesis (Ghosh et al, 2020). Future studies will be needed to elucidate the signal between oenocytes and fat body in response to muscle derived Pvf1.…”
Section: The Role Of Muscle In Maintaining Lipid Homeostasismentioning
confidence: 99%
“…Although in this study Pvf2 is shown to mediate intestinal antiviral immunity, its metabolic impact is not investigated yet. Interestingly, activation of Pvr, the receptor of Pvf2, in the fat body and oenocytes results in systemic lipid loss ( Zheng et al, 2017 ; Ghosh et al, 2019 ; Song et al, 2019 ), phenocopying the DCV infection and suggesting a Pvf2/Pvr axis in the gut-to-fat-body communication. Infection of other RNA viruses like Flock House virus (FHV) also leads to the decline of systemic lipid accumulation ( Chtarbanova et al, 2014 ), whether gut-peptide hormone is involved in FHV-associated metabolic disruption is an interesting question to address in the future.…”
Section: Gut Microbiota and Peptide-hormone Productionmentioning
confidence: 99%